Texture induced planar anisotropy of dwell fatigue response in titanium: Insights from experiments and crystal plasticity simulations. (May 2022) - Yazar, K.U.; Mishra, S.; Kumar, L.; Bahl, S.; Kumar, T. Kiran; Suwas, Satyam
Highlights: In plane anisotropy in the dwell fatigue behavior of cp-Ti was investigated. Higher dwell fatigue life was seen for rolling direction samples. Correlation of the dwell fatigue behavior with strain hardening and strain rate sensitivity was made. Contribution of strain hardening and strain rate sensitivity to the dwell fatigue behavior was deconvoluted. Abstract: This study elucidates the mechanism of texture induced planar anisotropy in ambient temperature (∼25 °C) dwell fatigue response of an annealed sheet of commercially pure titanium (cp-Ti). Dwell fatigue resistance on loading along rolling direction (RD) was observed to be markedly superior when compared to the loading along transverse direction (TD). Texture caused significant anisotropy in the strain hardening and strain rate sensitivity (SRS) which altered the dwell-fatigue response between RD and TD. RD direction had higher strain hardening and lower SRS both of which synergistically led to higher dwell-fatigue life compared to the TD direction. A combination of electron back scattered diffraction (EBSD) and Crystal Plasticity Fast Fourier Transform (CPFFT) simulations confirmed higher activity of prismatic slip in RD which led to higher strain hardening compared to TD. An analytical model was applied to deconvolute the contributions of strain hardening and SRS on dwell-fatigue life. The effect of strain hardening was observed to be higher when compared to that of SRS. The results of this work indicate that crystallographic texture is a remarkable tool to improve the dwell fatigue life of titanium. Graphical abstract: Image, graphical abstract